Reinterpreting Basic Ideas in Delivering Correctional Services: Making the Most of What We Have - Batastini, Ashley B. (The prison journal, 2025)
The United States’ correctional system is rife with treatment service delivery complications, resulting in significant gaps in access to care. As the field advocates for more substantial systemic changes, there is a need to think creatively about how to maximize available resources and skills to treat underserved clients with often complex and diverse needs. One strategy is to make better use of brief, intensive, and concentrated (BIC) interventions tailored to the needs of justice-involved people in correctional environments. This article reviews the barriers to providing correctional setting high-quality services, defines the role of BIC interventions in navigating these obstacles, explores existing theoretical and empirical support for BIC interventions, discusses recommendations and cautions for implementing BIC interventions, and highlights research needs to establish the effectiveness of BIC carceral interventions.